2018
DOI: 10.1021/acs.cgd.7b01746
|View full text |Cite
|
Sign up to set email alerts
|

Deracemization of NMPA via Temperature Cycles

Abstract: Recent studies have shown that total deracemization of a racemic suspension of a conglomerate forming compound can be attained in the presence of a racemizing agent through either attrition enhanced deracemization or temperature cycles. We experimentally investigate the deracemization of N-(2-methylbenzylidene)-phenylglycine amide, in the presence of DBU as racemizing agent in a mixture of isopropanol and acetonitrile (95/5 w/w), at several different operating conditions. Based on several experiments, we deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
129
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(137 citation statements)
references
References 37 publications
8
129
0
Order By: Relevance
“…This behaviour qualitatively rationalizes other results obtained experimentally for deracemization; for example, Breveglieri et al recently reported the deracemization of N-(2-methylbenzylidene)phenylglycine amide (NMPA) with DBU through temperature cycling, and concluded that a high operating temperature leads to fast deracemization. 15 Racemization of NMPA with DBU can be considered to be a catalytic reaction; consequently, the racemization rate is higher at higher operating temperatures. The faster deracemization kinetics at higher temperature for NMPA with DBU is, according to our interpretation, mostly due to the high racemization rate of NMPA.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…This behaviour qualitatively rationalizes other results obtained experimentally for deracemization; for example, Breveglieri et al recently reported the deracemization of N-(2-methylbenzylidene)phenylglycine amide (NMPA) with DBU through temperature cycling, and concluded that a high operating temperature leads to fast deracemization. 15 Racemization of NMPA with DBU can be considered to be a catalytic reaction; consequently, the racemization rate is higher at higher operating temperatures. The faster deracemization kinetics at higher temperature for NMPA with DBU is, according to our interpretation, mostly due to the high racemization rate of NMPA.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…14,15 In comparison, the productivity of TCID is as low as 0.1-5.0 g h -1 L -1 . 6,8 Thus, although TCID can double the theoretical yield, the productivity of the process is almost one order of magnitude lower than that of PC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, temperature-cycle-induced deracemization (TCID) is a process that converts a racemic mixture of the substrate to a nearly pure enantiomer in the solid phase without any external chiral source through temperature cycling. 1,[6][7][8][9][10][11] Scheme 1. Schematic representations of PC, TCID, and SOAT process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viedma ripening (VR) and temperature cycle‐induced deracemization (TCID) are key approaches to deracemization and are being actively studied. We recently reported that second‐order asymmetric transformation (SOAT), a combination of preferential crystallization (PC) and racemization, could achieve relatively high process productivity compared with TCID due to the short processing time.…”
Section: Introductionmentioning
confidence: 99%